Vertical Infestation of the Dengue Vectors Aedes aegypti and Aedes albopictus In Apartments In Kuala Lumpur, Malaysia - Muhammad Aidil, Roslan; Aziz, Shafie; Romano, Ngui; Yvonne Ai, Lian Lim; Wan Yusoff, Wan Sulaiman (The American Mosquito Control Association, 2013)
Dengue is a serious public health problem in Malaysia. The aim of this study was to compare the vertical infestation of Aedes population in 2 apartments in Kuala Lumpur with different status of dengue incidence (i.e., high-dengue-incidence area and area with no reported dengue cases). The study was also conducted to assess the relationship between environmental factors such as rainfall, temperature, and humidity and Aedes population that may influence Aedes infestation. Surveillance with a mosquito larvae trapping device was conducted for 28 continuous weeks (January to July 2012) in Vista Angkasa (VA) and Inderaloka (IL) apartments located in Kuala Lumpur, Malaysia. The results indicated that both Aedes spp. could be found from ground to higher floor levels of the apartments, with Aedes aegypti being more predominant than Ae. albopictus. Data based on mixed and single breeding of Aedes spp. on different floors did not show any significant difference. Both rainfall (R3; i.e., the amount of rainfall collected during the previous 3 wk before the surveillance period began) and RH data showed significant relationship with the number of Aedes larvae collected in VA and IL. No significant difference was found between the numbers of Aedes larvae in both study areas as well as maximum and minimum temperatures. Results also indicated adaptations of Ae. aegypti to the ecosystem at each elevation of high-rise buildings, with Ae. albopictus staying inside of apartment units.